Epidemiology and Pathophysiology of Multiple Sclerosis. Issue 4 (August 2022) - Ward, Melanie; Goldman, Myla D.
ABSTRACT: PURPOSE OF REVIEW: This article provides an overview of genetic, environmental, and lifestyle risk factors affecting the disease course of multiple sclerosis (MS) and reviews the pathophysiologic characteristics of both relapsing and progressive MS. RECENT FINDINGS: The prevalence of MS has increased in recent decades, and costs of care for patients with MS have risen dramatically. Black, Asian, and Hispanic individuals may be at risk for more severe MS-related disability. Multiple genetic MS risk factors have been identified. Factors such as low vitamin D levels and a history of Epstein-Barr virus, smoking, and obesity, especially during childhood, also influence MS risk. Traditionally thought to be a T-cell–mediated disease, recent research has highlighted the additional roles of B cells and microglia in both relapsing and progressive MS. SUMMARY: Complex interactions between genetic, environmental, and lifestyle factors affect the risk for MS as well as the disease course. People of color have historically been underrepresented in both MS clinical trials and literature, but current research is attempting to better clarify unique considerations in these groups. MS pathology consists of the focal inflammatory lesions that have been well characterized in relapsing MS, as well as a more widespread neurodegenerative component that is posited to drive progressive disease. Recent advances in characterization of both the inflammatory and neurodegenerative aspects of MS pathophysiology have yielded potential targets for future therapeutic options.